transform y=f(x) to y=f(x-1)

transform y=f(x) to y=f(x-1)

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

@ganeshie8

i need prove that it goes right to 1 unit

|dw:1436470728973:dw|

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.